Enhancement of optical limiting activity of para-aminobenzoic acid using silver nanoparticles - Shradha Lakhera; Meenakshi Rana; Vivek Dhuliya; L. P. Purohit; A. Dhanusha; T. C. Sabari Girisun; Shruti Sharma; Papia Chowdhury; Km Sakshi; Soumyendu Roy; Devendra Kumar (Scientific Reports)
Abstract An extensive study on the laser power limiting behavior of para-aminobenzoic acid (PABA) combined with silver nanoparticles (PABA + AgNPs) was done and reported in this article. The XRD spectra for PABA + AgNPs confirm its crystalline structure. The absorption spectra of AgNPs and PABA + AgNPs indicate complete stability of the samples. However, comparison of the absorption details indicated the occurrence of bathochromic shift in the PABA + AgNPs. The band gap of PABA was reduced after the introduction of AgNPs. Further, the Z-Scan experiment indicated the occurrence of reverse saturable absorption in prepared PABA + AgNPs. The linear transmittance of probe PABA (65%) was reduced to 52% after the addition of AgNPs. The overall study supported that the addition of AgNPs was suitably helpful in increasing the optical laser limiting capabilities of PABA. The results reported herein can be helpful in synthesizing an organic-nanoparticle optical laser limiting composite material and can be employed for the safety of optically sensitive devices.